NIGERIAN INSURANCE SECTOR & DIGITAL IMPERATIVE: A LEGAL RE-AWAKENING OCCASIONED BY COVID-19 VIRUS OUTBREAK - Toby, Boma Geoffrey; Ajie, Chukuma; Eriaye, Thompson John (PEOPLE: International Journal of Social Sciences, 2020)
The Insurance industry in Nigeria has come to terms with the need for a fully digitalized sector following the recent coronavirus COVID-19 outbreak in 2019/2020, which resulted to some partial and total lockdowns of the economic sectors at some point across the world. According to Mercatus Center (GMU), (2020) study, measures such as social distancing, closure of business places and the quarantining of people at home were being observed with adverse effects on insurance business operations in Nigeria. The lack of online technological infrastructure to maintain business amidst the pandemic and provide for necessary health policy coverages during the COVID-19 season was hugely felt and is the basis of this study. The pandemic changed the way insurers in Nigeria carried out their business operations. In the past, insurance marketing was done by a person to person contact and this has been in use but needs to change if insurers desire to reach out more to their clientele during periods of crises such as this. The inclusion of digital features to insurance buying and selling could demonstrate their higher purpose of providing protection and value to the public. The lack of complete digital infrastructure amidst the COVID-19 is an angle for insurers to reminisce on their services, how far-reaching and effective. The call for full digitalisation of the insurance sector is hereby made. The Insurance Act, 2004 also has not provided for any form of digital insurance services to improve on customer economy and remote services. The period of the pandemic has introduced a new normal in terms of how goods and services can be provided, in addition to the traditional person to person mechanism. This paper gives attention to all these and makes a case that the Nigerian insurance sector to introduce full digitalization of its operations to promote an all-inclusive market. Also, the law in force is reviewed to reflect this change.